Virile Condottieri On-screen and Emasculated Heroes on the Operatic Stage: Portraying Male Protagonists in Fascist Italy (1931-1937) - Cochran, Zoey (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2018)
Virility was central to Italian fascist ideology and yet the operas composed and performed in Italy during the 1930s systematically subvert the virility of their heroes both dramatically and musically, revealing a more fraught relationship with fascist ideology than has been suggested until now. A comparison between operas by Gian Francesco Malipiero, Ottorino Respighi, Pietro Mascagni, Ildebrando Pizzetti, and Alfredo Casella on the one hand and films by Alessandro Blasetti, Mario Camerini, and Carmine Gallone on the other, all produced in Italy during the mid-1930s, shows that the absence of male protagonists embodying fascist ideals of virility is confined to opera. I suggest that the failure of these operas to present virile male protagonists partly stems from a confrontation between opera and film. Indeed, the emergence of sound films and cinema’s privileged position within the Fascist regime forced opera to redefine itself as an art form in relationship to film.